The curative effect of androgen deprivation therapy alone is insufficient in high-risk prostate cancer. Issue 31 (6th August 2021) - Choi, Se Young; Lim, Bumjin; Chi, Byung Hoon; Lee, Wonchul; Kim, Jung Hoon; Kyung, Yoon Soo; You, Dalsan; Kim, Choung-Soo
Abstract : Abstract: To compare the outcomes of patients with high-risk prostate cancer treated by primary radical prostatectomy (RP) and primary androgen deprivation therapy (ADT). The study included patients with high-risk or very high-risk prostate cancer. Patients treated with definitive radiation therapy and those with clinical N1 and M1 disease were excluded. The RP group was divided into sub-cohorts of patients treated with ADT and those who received ADT after biochemical recurrence post-RP. Cancer-specific survival (CSS) and overall survival (OS) were analyzed using the Kaplan–Meier method and the Cox proportional hazards model. The study analyzed 859 patients divided into the RP group (n = 654) and ADT group (n = 205). Castration-resistant prostate cancer was detected in 23 (3.5%) patients in the RP group and 43 (21.0%) patients in the ADT group. Mortality cases included 63 (9.6%) patients in the RP group and 91 (44.4%) patients in the ADT group. CSS ( P = .0002) and OS ( P < .0001) were significantly higher in the RP group than in the ADT group. In the sub-cohort, CSS did not differ significantly between the RP and ADT groups, whereas OS was significantly higher in the RP group than in the ADT group ( P < .0001). In the multivariate analysis, primary ADT increased CSS (hazard ratio, 2.068; P = .0498) and OS (hazard ratio, 3.218; P < .0001) compared with RP. In clinically localized high-risk prostate cancer patients, primary RP was associated with better CSS and OS than primary ADT. Comprehensive counseling in this cohort of patients will help the selection of treatment.